ICT skills and use of digital tools for research in university teachers (Educational Knowledge, 2022)
The public university is immersed in a process of constant change due to the epidemiological situation presented by the Covid-19 pandemic. Higher education faculty have been involved in the necessary changes to ensure the continuity of classes through virtual learning, utilizing information and communication technologies (ICTs) as digital tools for research.The purpose of this study was to understand the ICT competencies of faculty members and their use of digital tools for academic processes, research, and management at the National University of Pilar in Paraguay. A qualitative approach was chosen, employing a multiple case study methodology. The sample was selected based on a purposive homogeneity and consisted of five faculty members from the Systems Analysis program in the technical areas.These faculty members possess ICT competencies and utilize digital tools for their academic activities, research, and information management. They exchange experiences, knowledge and practices with peers and colleagues, strengthening network learning.
Keywords: ICT skills; digital tools; higher education; research